Pengaruh Inflasi, Suku Bunga, Nilai Tukar dan Produk Domestik Bruto Terhadap Return Saham Sektor Pertanian dan Sektor Pertambangan Periode 2009 – 2019 - Dyah Saputri; Tahmat Tahmat; Erna Garnia; Deden Rizal (Jurnal Ekonomi Manajemen Perbankan, 2020)
This study aims to determine the effect of inflation, interest rates, exchange rates, and gross domestic product on stock returns in the agricultural and mining sectors companies listed on the Indonesia Stock Exchange (IDX) for the period 2009 – 2019 either partially or simultaneously. The sampling technique used in this study was purposive sampling, and there were 12 companies that were used at research objects. This research used the quantitative research method using panel data regression analysis method. The result showed that partially inflation and exchange rates have a significant negative effect on stock returns, while interest rates and gross domestic product have no effect on stock returns. Based on the results of the simultaneousl inflation, interest rates, exchange rates, and gross domestic product have a effect on stock returns. Keywords: Inflation, Interest Rates, Exchange Rates, and Gross Domestic Product and Stock Return